Investigation of Torque Teno Virus (TTV) DNA as an immunological and virological marker in pediatric hematopoietic stem cell transplantation (HSCT) patients. (December 2020) - Peker, Bilal Olcay; Daloğlu, Aylin Erman; Görzer, Irene; Puchhammer-Stöckl, Elisabeth; Parkan, Ömür Mustafa; Akbaş, Hilal; Kintrup, Gülen Tüysüz; Mutlu, Derya; Küpesiz, Osman Alphan; Çolak, Dilek
Abstract: Background: High viral loads are observed in Torque Teno Virus (TTV) infection after hematopoietic stem cell transplantation (HSCT). We aimed to analyze the kinetics of plasma TTV-DNA load in pediatric patients who received immunosuppressive therapy and developed infection complications in the first 100 days after HSCT. Methods: As a patient group; 113 plasma samples taken from 33 pediatric HSCT recipients at a time interval after transplantation and as a control group; 38 plasma samples from 38 children without known chronic disease were included in the study. Viral nucleic acid isolation was performed by using the NucliSENS easyMAG (bioMerieux, France) system. A laboratory designed quantitative polymerase chain reaction process was performed on 7300 Real-Time PCR system (Applied Biosystems, CA, USA) with the amplification mixture containing primer and probe sequences for the UTR gene region. Results: TTV-DNA was detected in all patient's samples and the median viral load was calculated as 7.67 Log10 copies/mL (range: 2.84–9.59). In the control group, the TTV-DNA median viral load was calculated as 5.51 Log10 copies/mL (range: 2.50–7.04), except for one negative sample. A significant difference was observed between the control group and the patient group in terms of TTV viral load levels. In nine patients, a median 2.15 Log10 copies/mL viral load increase was observed at 31–60 days post-transplant compared to the pre-transplant period. Conclusion: TTV-DNA levels should be closely monitored to understand the immune status of the first 100 days after transplantation and the effects of treatment regimens on patients with HSCT. Highlights: TTV is an immunological biomarker with the potential to improve treatment follow-up in HSCT patients. TTV-DNA loads show fluctuations depending on the immunological status in the early period after transplantation. Considering high viral shedding of TTV in pediatric age, cut-off values should be determined to guide follow-up in immunosuppressive patients.